Evolutionary loss of light-harvesting proteins Lhcb6 and Lhcb3 in major land plant groups--break-up of current dogma - Kouřil, Roman; Nosek, Lukáš; Bartoš, Jan; Boekema, Egbert J; Ilík, Petr (New phytologist, 2016)
Photosynthesis in plants and algae relies on the coordinated function of photosystems (PS) I and II. Their efficiency is augmented by finely-tuned light-harvesting proteins (Lhcs) connected to them. The most recent Lhcs (in evolutionary terms), Lhcb6 and Lhcb3, evolved during the transition of plants from water to land and have so far been considered to be an essential characteristic of land plants. We used single particle electron microscopy and sequence analysis to study architecture and composition of PSII supercomplex from Norway spruce and related species. We have found that there are major land plant families that lack functional lhcb6 and lhcb3 genes, which notably changes the organization of PSII supercomplexes. The Lhcb6 and Lhcb3 proteins have been lost in the gymnosperm genera Picea and Pinus (family Pinaceae) and Gnetum (Gnetales). We also revealed that the absence of these proteins in Norway spruce modifies the PSII supercomplex in such a way that it resembles its counterpart in the alga Chlamydomonas reinhardtii, an evolutionarily older organism. Our results break a deep-rooted concept of Lhcb6 and Lhcb3 proteins being the essential characteristic of land plants, and beg the question of what the evolutionary benefit of their loss could be.
Keywords: podjednotky proteinů; fotosystém II (proteinový komplex); rostlinné proteiny; Photosystem II Protein Complex; Plant Proteins; Phylogeny; vyšší rostliny; Sequence Homology, Amino Acid; rostlinné geny; světlosběrné proteinové komplexy; biologická evoluce; Biological Evolution; fylogeneze; sekvenční homologie aminokyselin; Embryophyta; Genes, Plant; Protein Subunits; Light-Harvesting Protein Complexes